Engineering and Application of Pluripotent Stem Cells - Martin, Ulrich; Zweigerdt, Robert; Gruh, Ina.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reviews the latest biotechnological advances with pluripotent stem cells, exploring their application in tissue engineering and medicinal chemistry. Chapters from expert contributors cover topics such as the production of transgene-free induced pluripotent stem cells (iPSCs), expansion, controlled differentiation and programming of pluripotent stem cells, and their genetic instability. Particular attention is given to the application of the pluripotent stem cells for vascularision of engineered tissue and for drug screening. This book will appeal to researchers working in regenerative medicine and drug discovery, and to bioengineers and professionals interested in stem cell research.
Nonintegrating Human Somatic Cell Reprogramming Methods -- Scalable Expansion of Pluripotent Stem Cells -- Scalable Cardiac Differentiation of Pluripotent Stem Cells Using Specific Growth Factors and Small Molecules -- Specific Cell (Re-)Programming: Approaches and Perspectives -- Bioengineered Cardiac Tissue Based 4 on Human Stem Cells for Clinical Application -- Human Pluripotent Stem Cells to Engineer Blood Vessels -- Targeted Gene Editing in Human Pluripotent Stem Cells Using Site-Specific Nucleases -- Acquired Genetic and Epigenetic Variation in Human Pluripotent Stem Cells -- Requirements for Using iPSC-Based Cell Models for Assay Development in Drug Discovery.
Keywords: Biotechnology; Stem cells; Biomedical engineering; Medicinal chemistry; Regenerative medicine; Biotechnology; Stem Cell Biology; Biomedical Engineering and Bioengineering; Medicinal Chemistry; Regenerative Medicine and Tissue Engineering